2017
DOI: 10.1039/c7ta01812f
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput screening of bimetallic catalysts enabled by machine learning

Abstract: We present a holistic machine-learning framework for rapid screening of bimetallic catalysts with the aid of the descriptor-based kinetic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
283
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(300 citation statements)
references
References 50 publications
4
283
0
1
Order By: Relevance
“…This low error is within the screening energy range of potential catalysts. Similar features have been used in the prediction of CO and OH adsorption on bimetallic surfaces to identify several transition metal alloys and local environments with theoretical performance better than Pt in direct methanol fuel cells . Similarly, Gasper et al have studied the CO adsorption on the Pt nanoparticles using a ML approach.…”
Section: Applicationmentioning
confidence: 99%
“…This low error is within the screening energy range of potential catalysts. Similar features have been used in the prediction of CO and OH adsorption on bimetallic surfaces to identify several transition metal alloys and local environments with theoretical performance better than Pt in direct methanol fuel cells . Similarly, Gasper et al have studied the CO adsorption on the Pt nanoparticles using a ML approach.…”
Section: Applicationmentioning
confidence: 99%
“…Predictive models of adsorption energies of common catalytic descriptors like OH*, CO*, or NO* on multimetallic surfaces have flourished in the past years. These models can be roughly assigned to physics‐based and data‐driven approaches. While the former approaches start their predictions from pre‐determined physical models, like the d ‐band theory, bond order conservation, or electrostatic interactions, the latter use large sets of materials properties and try to identify and use trends that might not have a known analytical expression .…”
Section: Recent Trendsmentioning
confidence: 99%
“…Ma et al . and Li et al . trained artificial neural networks with sets of DFT‐calculated adsorption energies and electronic structure fingerprints like e. g. moments of the d ‐band distribution.…”
Section: Recent Trendsmentioning
confidence: 99%
“…As outlined in Section , having a physically relevant and easily accessible features is crucial to build models for catalyst screening applications as data representation could dramatically influence ML performance . In another study, p‐band and d‐band characteristics of an adsorption site were found as the key features describing the capabilities of bimetallics in breaking energy‐scaling constraints of *CO . A noticeable contribution was found from d‐band shape and sp‐band filling, which is typically ignored in simplistic d‐band model.…”
Section: Machine Learning In Co2rrmentioning
confidence: 99%